2010
DOI: 10.1128/cvi.00195-10
|View full text |Cite
|
Sign up to set email alerts
|

Increased Allergic Immune Response toSarcoptes scabieiAntigens in Crusted versus Ordinary Scabies

Abstract: Scabies, a parasitic skin infestation by the burrowing "itch" mite Sarcoptes scabiei, causes significant health problems for children and adults worldwide. Crusted scabies is a particularly severe form of scabies in which mites multiply into the millions, causing extensive skin crusting. The symptoms and signs of scabies suggest host immunity to the scabies mite, but the specific resistant response in humans remains largely uncharacterized. We used 4 scabies mite recombinant proteins with sequence homology to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
123
1
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(141 citation statements)
references
References 43 publications
6
123
1
11
Order By: Relevance
“…It has been suggested that a Th2-biased immune response against S. scabiei infection may account for the development of crusted scabies. Extremely high levels of IgE antibody have been reported in patients with crusted scabies, indicative of a Th2-biased immune response (5,6,15,32). However, studies in goat and sheep models suggested that high IgE levels may indicate protective immune responses (33,34), and thus high levels of IgE may therefore not be directly related to a dysregulated immune response leading to the development of crusted scabies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been suggested that a Th2-biased immune response against S. scabiei infection may account for the development of crusted scabies. Extremely high levels of IgE antibody have been reported in patients with crusted scabies, indicative of a Th2-biased immune response (5,6,15,32). However, studies in goat and sheep models suggested that high IgE levels may indicate protective immune responses (33,34), and thus high levels of IgE may therefore not be directly related to a dysregulated immune response leading to the development of crusted scabies.…”
Section: Discussionmentioning
confidence: 91%
“…It has been suggested that a Th2-biased immune response in S. scabiei infestation may account for the development of crusted scabies (6,11). Peripheral blood mononuclear cells (PBMCs) isolated from patients with crusted scabies secreted higher levels of IL-4, IL-5 and IL-13, and lower levels of IFNc, compared to those of ordinary scabies patients; levels of total and antigenspecific IgE are also higher in crusted scabies patients (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 98%
“…5 A produção de IL-17 estará ainda na dependência da produção por linfócitos Tγδ e será aumentada por níveis reduzidos de IL-10 e TGF-β1 (célu-las T reguladoras). 3,4,6 Adicionalmente, existe uma migração predominante de linfócitos T CD8+ para a derme e quase ausência de linfócitos B.…”
Section: Discussionunclassified
“…Doentes com sarna crostosa apresentam níveis séricos mais elevados de IgE e IgG4 do que doentes com formas clássicas da doença. 5,7 Este switch de um predomínio de resposta imunológica baseada em linfócitos Th1 para uma resposta menos eficaz baseada em linfócitos Th2 acontece ao longo da evolução da infecção VIH, estando relacionado com a evolução para SIDA. 8 Desta forma se poderá explicar a maior prevalência de sarna crostosa na população imunodeprimida por infecção pelo VIH.…”
Section: Discussionunclassified
“…The antibody response to S. scabiei infestation has been documented in human (Walton et al, 2010) and animal species (Bornstein and Zakrisson, 1993;Arlian et al, 1994Arlian et al, , 1996Bornstein et al, 1995;Little et al, 1998;Arlian and Morgan, 2000;Sarasa et al, 2010;Rodríguez-Cadenas et al, 2010). ELISA tests, based on standard whole mite extracts with multiple mite antigens, which demonstrate specific antibodies to S. scabiei in different host species such as dogs, cats, camels, pigs, chamois, and red foxes have been used as reliable simple diagnostic tools (Bornstein et al, 1996(Bornstein et al, , 2006Hollanders et al, 1997;Van der Heijden et al, 2000;Lower et al, 2001;Rambozzi et al, 2004;Malik et al, 2006).…”
Section: Introductionmentioning
confidence: 99%